Rethinking phenylalanine levels in phenylketonuria for optimal neurocognitive development beyond childhood - Câmara, Beatriz; Florindo, Cristina; de Lima, Cláudia Bandeira; Correia, Nélia; Fernandes, Inês; Batista, Manuela; Gaspar, Ana; Janeiro, Patrícia (Frontiers in Pediatrics, 2025)
IntroductionPhenylketonuria (PKU) is an inborn error of phenylalanine (Phe) metabolism that disrupts neurotransmitter balance. Although early intervention has improved outcomes, neurocognitive challenges persist, particularly during adolescence. Metabolic control guidelines for patients aged >12 years differ between the European Union and the United States, with recommended blood Phe levels below 600 µM and 360 µM, respectively.MethodsThis study evaluated the relationship between blood Phe levels, intelligence quotient (IQ), and executive functions using the Wechsler Intelligence Scale for Children-Third Edition and the d2 Test of Attention. Blood Phe levels were monitored longitudinally and summarized using the Index of Dietary Control (IDC), calculated as the mean of individual annual median Phe concentrations, both before and after 12 years of age.ResultsThe study included 14 early-treated PKU patients aged 12–17 years, all diagnosed through newborn screening programs. Participants maintained good metabolic control (IDC <360 µM) prior to 12 years of age, with a mean IDC of 302 µM. Higher IQ scores before the age of 12 years were observed only among patients with consistent dietary compliance. After that age, attentional performance declined in those who were noncompliant with dietary recommendations. Additionally, occasional elevations in blood Phe levels at the time of cognitive assessments were associated with poorer cognitive performance.DiscussionThese findings underscore the detrimental effects of elevated Phe levels on executive functions during adolescence and highlight the need for larger studies to determine whether blood Phe levels between 360 and 600 µM are safe for patients aged >12 years.